Noise-induced ribbon synapse loss in the mouse basal cochlear region does not reduce inner hair cell exocytosis - Oestreicher, David; Malpede, Alfonso Mauro; Reitmeier, Annalena; Bräuer, Carolin Paula; Schoch, Laura; Strenzke, Nicola; Pangrsic, Tina (Frontiers in Cellular Neuroscience, 2025)
Noise-induced hearing loss is one of the most common forms of hearing loss in adults and also one of the most common occupational diseases. Extensive previous work has shown that the highly sensitive synapses of the inner hair cells (IHCs) may be the first target for irreparable damage and permanent loss in the noise-exposed cochlea, more precisely in the cochlear base. However, how such synaptic loss affects the synaptic physiology of the IHCs in this particularly vulnerable part of the cochlea has not yet been investigated. To address this question, we exposed 3–4-week-old C57BL/6J mice to 8–16 kHz noise for 2 h under isoflurane anesthesia. We then employed hearing measurements, immunohistochemistry and patch-clamp to assess IHC synaptic function. Two noise sound pressure levels (SPLs) were used to evoke acute hearing threshold elevations with different levels of recovery 2 weeks post-exposure. Regardless of noise intensity, the exposure resulted in a loss of approximately 25–36% of ribbon synapses in the basal portions of the cochlea that persisted 2 weeks after exposure. Perforated patch-clamp recordings were made in the IHCs of the basal regions of the cochlea where the greatest synaptic losses were observed. Depolarization-evoked calcium currents in IHCs 2 weeks after exposure were slightly but not significantly smaller as compared to controls from age-matched non-exposed animals. Exocytic changes monitored as changes in membrane capacitance did not follow that trend and remained similar to controls despite significant loss of ribbons, likely reflecting increased exocytosis at the remaining synapses. Additionally, we report for the first time that acute application of isoflurane reduces IHC calcium currents, which may have implications for noise-induced IHC synaptic loss.